COLOSTRUM SUPPLEMENTATION IN ATHLETES: EFFECTS ON PERFORMANCE, IMMUNITY, AND RECOVERY - Lidia Mądrzak; Bartłomiej Roszkowski; Marta Korchowiec; Wiktor Chrzanowski; Katarzyna Krzyżanowska; Łukasz Bialic; Władysław Hryniuk; Julia Kwiecińska; Jacek Sitkiewicz; Alicja Toczyłowska; Mateusz Muras (International Journal of Innovative Technologies in Social Science, 2025)
Objective: Bovine colostrum (BC) is the first milk produced by cows in the initial days after calving. It is a nutrient-rich fluid formulated to support neonatal growth and immunity. Its composition includes immunoglobulins (mainly IgG), growth factors, antimicrobial peptides (e.g., lactoferrin, lysozyme, lactoperoxidase), cytokines, oligosaccharides, and essential vitamins, minerals, and macronutrients. This review aims to evaluate the effectiveness of bovine colostrum supplementation in athletes, particularly in the context of performance, immune function, and gut health.Methods: All data were collected from publicly available sources. This article's databases were accessed via PubMed, Scopus, and Web of Science.Key findings: In recent decades, BC has gained interest in sports nutrition due to its potential benefits beyond early development. In athletes, colostrum may help support post-exercise recovery, enhance immune function under physical stress, and protect against exercise-induced intestinal permeability. Evidence also suggests it may reduce the incidence of upper respiratory tract infections and inflammation, while helping maintain gut barrier integrity. These mechanisms may indirectly improve athletic performance and reduce training disruptions.Conclusion: Bovine colostrum appears to support gut integrity, immune resilience, and recovery in athletes. Its potential impact on performance is likely secondary to these health benefits. However, further high-quality studies are needed to confirm efficacy and define optimal dosing protocols in sports nutrition.